2018
DOI: 10.3897/compcytogen.v12i3.22590
|View full text |Cite
|
Sign up to set email alerts
|

Karyotypic variation in the long-whiskered catfish Pimelodus blochii Valenciennes, 1840 (Siluriformes, Pimelodidae) from the lower Tapajós, Amazonas and Trombetas Rivers

Abstract: The genus Pimelodus LaCépède, 1803 comprises 35 formally recognized species distributed along the major neotropical river basins. Despite conservatism in diploid number with 2n=56, an intense variation of chromosomal morphology (karyotypic formula) has been documented in Pimelodus species. In the present study, we analyzed karyotypes of 20 specimens, identified as Pimelodusblochii Valenciennes, 1840 and collected from the lower courses of the Tapajós, Amazonas and Trombetas Rivers. The karyotypes were characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…However, several groups of Neotropical fish carry these ribosomal genes in synteny, distant or colocalized. Several recent studies in Siluriformes showed the synteny of these genes (e.g., Baumgärtner et al, 2018;Fonseca et al, 2018;Lorscheider et al, 2018;Takagui et al, 2019;Terra et al, 2019), being considered as a plesiomorphic feature in Tricomycteridae and Loricariidae (Ziemniczak et al, 2012), and an ancestral condition in the sister group of Auchenipteridae, the Doradidae family (Baumgärtner et al, 2018;Takagui et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, several groups of Neotropical fish carry these ribosomal genes in synteny, distant or colocalized. Several recent studies in Siluriformes showed the synteny of these genes (e.g., Baumgärtner et al, 2018;Fonseca et al, 2018;Lorscheider et al, 2018;Takagui et al, 2019;Terra et al, 2019), being considered as a plesiomorphic feature in Tricomycteridae and Loricariidae (Ziemniczak et al, 2012), and an ancestral condition in the sister group of Auchenipteridae, the Doradidae family (Baumgärtner et al, 2018;Takagui et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Despite that, a great amount of fish species has never been biologically or genetically studied. Recent findings showed efforts to cytogenetically characterize Pimelodidae species in the Amazonian region, providing important data for this group of fishes, as the described for Pimelodus (Fonseca et al 2018) and the giant catfishes Phractocephalus hemioliopterus (Swarça et al 2017) and Brachyplatystoma filamentosum (Gonçalvez et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A number of phylogenetic studies have demonstrated the complexity of this taxon, which still has unresolved questions on the status of species and their monophyly. In addition, the species with a more ample distribution, such as Pimelodus blochii Valenciennes, 1840, Pimelodus pictus Steindachner, 1876, and Pimelodus ornatus Kner, 1858, appear to represent species complexes [ 7 , 8 , 13 ].…”
Section: Introductionmentioning
confidence: 99%